Evaluating the Transformative Digital Pedagogies for Higher Education Training Programme: Insights into Participants’ Perceptions - Kakoulli-Constantinou, Elis; Soule, Maria Victoria; Hadjiconstantinou, Stavroulla; Pantela, Nicoletta (My University, 2025)
The adaptation of education and training systems to the digital age is one of the priorities of the European Commission. Aiming at promoting high-quality, inclusive education, Higher Education (HE) institutions are working towards digital and pedagogical transformation; however, lack of both pedagogical skills for using digital technologies and digital skills for implementing innovative teaching practices make this a challenging task. The Erasmus+ funded Transformative Digital Pedagogies for Higher Education (TDP4HE) project addresses this challenge by developing a training programme for HE staff designed to enhance academic staff’s pedagogical and digital competencies, enabling them to effectively transition to digital education. This paper examines the first implementation and evaluation of this online training programme, delivered to EUt + university staff in May-June 2024. The results show participants’ positive perceptions about the training programme’s innovative approach to transformative digital pedagogies. They also identify certain challenges encountered and reveal ways in which the training programme could be improved to better meet educators’ needs.